Chandelier retroillumination-assisted cataract surgery in two cases of congenital aniridia with severe aniridia-associated keratopathy: case series - Joseph Hu; Chao-Chien Hu (Therapeutic Advances in Ophthalmology)
Congenital aniridia is a rare genetic eye disorder often associated with PAX6 gene mutations, leading to complex ocular manifestations, including aniridia-associated keratopathy (AAK) and cataracts. The surgical management of cataracts in these patients is particularly challenging due to severe corneal opacities, which obscure key surgical steps such as capsulorhexis and phacoemulsification. This report presents two cases of congenital aniridia with severe AAK, in which chandelier retroillumination-assisted cataract surgery was employed. This technique, typically used in vitreous surgery, provided enhanced visualization of the lens through posterior segment illumination, facilitating successful cataract extraction and intraocular lens implantation. Both patients showed significant postoperative improvement in visual acuity. These cases demonstrate the feasibility and effectiveness of chandelier retroillumination-assisted cataract surgery in patients with congenital aniridia complicated by severe corneal opacity.